The Role of Market Transparency and Regulation on Investor Protection and Risk Management in Crypto Assets in Jawa Barat - Fera Lufhidarani Pranita; Achmad Choerudin; Arnes Yuli Vandika (West Science Interdisciplinary Studies, 2024)
The rapid expansion of the crypto asset market presents significant challenges related to market transparency, regulation, and risk management. This study investigates the relationships between market transparency, investor protection regulations, and risk management in shaping investor confidence in West Java. Using a quantitative approach, data was collected from 195 active crypto investors through a Likert-scale questionnaire and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results reveal that market transparency and regulation significantly influence investor protection and risk management, with regulation demonstrating the strongest impact. The findings highlight the synergistic role of transparency and regulation in fostering a stable and secure crypto market. This research provides valuable insights for policymakers, regulators, and market participants to enhance market integrity and investor confidence. Recommendations include strengthening transparency practices, harmonizing regulations with global standards, and integrating advanced risk management tools to mitigate uncertainties.